Design of a dual-band butler matrix - Zhu, Jian. (2010)
This report presents the design of a dual-band Butler Matrix to be used in cellular communication systems and it covers two frequency bands at 900MHz and 1800MHz. The Butler Matrix is one of the most widely used Switched Beam Network and it can be used to feed the antenna array. Design and measure of the individual dual-band components which compose the Butler matrix are also presented. Those components are: quadrature hybrid, crossover (0 dB) coupler and phase shifter. The experimental results show that the return loss is between -19.4dB and -28.9dB, the coupling factor is between -7.2dB and -9.6dB, the isolation losses are better than -20dB and phase error at 900MHz is ± 5.8 degrees while phase error at 1800MHz is ± 7.8 degrees.